The Effect Of The Project Based Learning Model On Students' Critical Thinking Skills In Economics In Grade X - Mawar Gultom; Mian Siahaan; Nova Yunita Sari Siahaan (STABN RADEN WIJAYA WONOGIRI, 2025)
This experimental study aimed to determine the effect of the project-based learning model on students' critical thinking skills in Economics in tenth-grade students at SMA Indonesia Membangun Medan. The research method used was quantitative with a quasi-experimental design. The sample consisted of 62 tenth-grade students divided into two groups: an experimental class (X-2, 32 students) using the project-based learning model and a control class (X-1, 30 students) using the conventional learning model. The instrument used was a critical thinking skills questionnaire referring to six indicators according to Mardiana (2024). The results showed a difference between the critical thinking skills of students in the experimental and control classes. The t-test showed that t_(count )14.067 > t_(tabel )3, thus accepting the alternative hypothesis. Therefore, it can be concluded that the project-based learning model has a positive and significant effect on students' critical thinking skills in economics.